An omics perspective to the molecular mechanisms of anticancer metallo-drugs in the computational microscope era. (3rd August 2017) - Spinello, Angelo; Magistrato, Alessandra
ABSTRACT: Introduction : Metallo-drugs have attracted enormous interest for cancer treatment. The achievements of this drug-type are summarized by the success story of cisplatin. That being said, there have been many drawbacks with its clinical use, which prompted decades worth of research efforts to move towards safer and more effective agents, either containing platinum or different metals. Areas covered : In this review, the authors provide an atomistic picture of the molecular mechanisms involving selected metallo-drugs from structural and molecular simulation studies. They also provide an omics perspective, pointing out many unsettled aspects of the most relevant families of metallo-drugs at an epigenetic level. Expert opinion : Molecular simulations are able to provide detailed information at atomistic and temporal (ps) resolutions that are rarely accessible to experiments. The increasing accuracy of computational methods and the growing performance of computational platforms, allow us to mirror wet lab experiments in silico . Consequently, the molecular mechanisms of drugs action/failure can be directly viewed on a computer screen, like a 'computational microscope', allowing us to harness this knowledge for the design of the next-generation of metallo-drugs.